The application of Environmental Impact Assessment (EIA) in granting planning approval at local authorities / Hasnizam Ab Dulhamid - Ab Dulhamid, Hasnizam (2011)
Environmental Impact Assessment (EIA), the subject of this study, has been in operation in Malaysia form more than two decades as the Environmental Quality (Prescribed Activities) (Environmental Impact Assessment) Order 1987 was formally introduced in April 1988. The EIA Malaysia procedure identifies two parties that are responsible to grant approval for development or project proposals, namely the State Planning and Development Committee and the National Industrial Development Committee, depending on the types of the development proposals. On the other hand, EIA must also be utilized in the approval of project design and in the process of issuing licenses and permits by various government agencies including the process of granting the planning approval at Local Authorities. However, to date there is no research conducted on the application of EIA in granting the planning approval. The purpose of this study is to examine the utilization of Environmental Impact Assessment (EIA) in granting the planning approval at Local Authorities. The research involved three Local Authorities in Perak State as case studies. This research also provides the proposals to improve the application of EIA in granting the planning approval.